Teacher Influencers' Speeches on Accelerating the Transformation of Micro-Celebrity Teachers on Instagram - Syofia Ulfah; Yurni; Yusrizal; Syifa Khairunnisa (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2026)
The rapid development of social media has shifted the role of teachers from formal educators in the classroom to digital public figures who actively produce educational content. This study aims to identify the forms of speech acts (locutionary, illocutionary, perlocutionary) of teacher influencers on Instagram and analyze their contribution to the construction of micro-celebrity identities. Using an interpretive qualitative approach, this study examines eight purposively selected teacher influencers. The research data includes verbal texts and paralinguistic elements from videos, captions, netizen comments, and highlight features. The findings indicate that in the study of digital pragmatics, speech acts occur multimodally with a dominant illocutionary function, while perlocutionary effects reach a wider social area due to the influence of social media algorithms. Language is no longer merely a means of communication, but an instrument for shaping digital images and influence. These speech acts function as interpersonal communication strategies that transform formal pedagogical relationships into relational ones. Overall, the perlocutionary effects prove that the identity of teacher micro-celebrities is not constructed unilaterally, but is co-constructed by the communicator and the audience. Instagram ultimately serves as a space for the transformation of the teaching profession: from conventional classroom instructors to public communicators and digital authority figures in the field of education.